Effect of Emotional Intelligence and Transformational Leadership on Employee Performance Mediated by Employee Job Satisfaction - Putri Ramadhona; Erlina, Erlina; Jimad, Habibullah (FEB - Universitas Lampung, 2022)
This study aims to see the direct effect of Emotional Intelligent and Transformational Leadership on employee performance and job satisfaction, the direct effect of job satisfaction on employee performance, and whether job satisfaction mediates the direct effect of Emotional Intelligent and Transformational Leadership on employee performance at PT. Surya Tsabat Mandiri. This research was conducted using a quantitative approach with survey methods and probability sampling techniques. The instruments were previously tested using the SPSS tool, and hypothesis testing and research data were analyzed using SEM on SmartPLS software version 3.2.9. The results showed that Emotional Intelligent had a positive and significant direct effect on employee satisfaction and performance, in contrast to Transformational Leadership, which only had a positive and significant direct effect on employee job satisfaction but a negative and insignificant on employee performance. On the other hand, job satisfaction has a positive and significant direct effect on employee performance. Further results show that job satisfaction mediates the direct effect of Emotional Intelligent and Transformational Leadership on employee performance. Keywords: Emotional Intelligence, Transformational leadership, Job Satisfaction, Employee Performance